Investigation of influence of defectiveness in aluminous porcelain structure on fracture process under compressive loading using acoustic emission method - Ranachowski, Przemysław; Rejmund, Feliks; Pawełek, A.; Piątkowski, A. (Archives of Acoustics, 2006)
This work presents acoustic emission (AE) and microscopic study of ceramic samples subjected to compressive stress. The object of research were specimens made of insulator aluminous porcelain 130 type. Purpose of this work was registration the stages of the process of degradation in ceramic material structure. Microscopic study allowed observing structural parameters of material before loading and on particular stages of the process of defects development. Influence of technological faults existing in material structure on mechanical-acoustic characteristics and mechanical strength of the samples was recognized.